Pengembangan panduan konseling kelompok model SFBC Untuk menurunkan perilaku prokrastinasi akademik siswa sekolah menengah pertama - Dharmapatni, Dewa Ayu Sri; Putri, Dewi Arum Widhayanti Metra; Suranata, Kadek (Jurnal EDUCATIO: Jurnal Pendidikan Indonesia, 2024)
TheI aIim of the sreseIarch isI to deIveIlop and  teIst the cIonteInt valIiIdity and eIffeIctiveInesse oif the SIFBC grouIp counseIliIng guIidIebook to redIuce acadIemic procrastIinatIion beIhaviIor of jIunIior hiIgh scIhool stludents. This relsearch is a devellopmenlt resealrch that adlapts the  ADDIlEl devellopmenlt processl .This reselarch hasl gonel thlrough a clonltelnt vallidlity telst usels 5 expelrts asl elxpelrts. Daltal colllectionl inl thisl validlity telst wals carriedl out usinlg elxpelrt vallidlity instrumelnts wlhich welre alnallyzed ulsing thel CVRl alnd CVIl formlulasl als wlell als thle t-telst. thel relsullts of CVRl = 24 and CVIl = 1 this is inclludedl inl the speciall catelgory. Thel elffectivelness telst in thlis studly wals carrield out on a llimited basils withl 10 class VIII studelnts at SMP N 1 Tegallalang as reselarch subjelcts, using a one group pre-test and post-test design experiment. The results of the t-test were obtainedl, namelly tcounlt of 7.049 with df = 9 at a signlificance lelvell of 0.05. Obtained t-table of 2.262 then tcount > ttable so that Ho is rejelcteld. So thisl SFBlC group coulnseling guidelbook caln be declareld effelctive in relducing the procrastIinatIion belhavior of julnlior hligh sclhool stuldelnts.